School-Based 4-H Programming Series: Setting Schools Up for Success - Vanessa Spero (EDIS)
Success at school-based sites to form 4-H clubs and programs will depend on utilizing the developmental practices of positive youth development and incorporating a set of principles known as the Essential Elements. Youth benefit from feeling like they belong, mastering a skill, gaining independence, and exhibiting generosity. The 4-H club atmosphere provides a setting for youth to achieve lifelong skills as long as they are given the opportunity to learn them. This new 4-page publication of the UF/IFAS 4-H Youth and Development Program was written by Vanessa Spero-Swingle. https://edis.ifas.ufl.edu/4h405